Seismogenic sources and stress pattern in Costa Rica inferred from focal mechanisms during 2025 - Linkimer, Lepolt (2026)
This study presents an analysis of seismicity patterns, focal mechanisms, and the regional stress field inferred from seismic activity recorded in Costa Rica during 2025. Throughout the year, the National Seismological Network (RSN) located 5,781 earthquakes, whose cumulative seismic energy release is equivalent to a moment magnitude (Mw) 6.6 event. Of this total, 181 earthquakes (~3.1%) were perceived by the population. A total of 125 new focal mechanisms were calculated and, together with the spatial and depth distribution of the events, allowed their tectonic origin to be classified into four main categories: shallow (<35 km) crustal faulting within the overriding Caribbean and Panama plates, the interplate seismogenic zone of the Cocos Plate subduction, internal deformation of the subducting Cocos Plate, and faulting associated with the boundary between the Cocos and Nazca plates. Earthquakes related to crustal faulting were predominantly characterized by strike-slip mechanisms, whereas interplate events exhibited reverse faulting consistent with the geometry of the subduction interface. Analysis of sub-horizontal P and T axes indicates a coherent regional stress field, characterized by maximum compression oriented predominantly northeast-southwest and maximum extension approximately northwest-southeast, with local rotations reflecting the tectonic complexity of the region. The largest earthquakes reached Mw 6.1 and originated both within the interplate zone and along the Cocos–Nazca plate boundary. The maximum documented intensity was VI (MMI), observed only for the Quepos earthquake on October 21, while the remaining felt events produced moderate intensities and localized effects.